KEANEKARAGAMAN DAN KELIMPAHAN ARTHROPODA PENGUJUNG TANAMAN SAWI DENGAN APLIKASI PUPUK HAYATI PLANT GROWTH PROMOTING RHIZOBACTERIA - Hilwa Walida (JURNAL AGROPLASMA, 2019)
Unwise use of pesticides have some negative impacts on the environment. The impact of unwise use of pesticides will certainly cause serious problems for the agricultural world. Plant Growth Promoting Rhizobacteria (PGPR) can be one of the solutions of dependence on synthetic chemical fertilizer and pesticide products. This study aims to determine the effect of PGPR biological application on the diversity and abundance of Arthropod visitors of mustard plants. This research was conducted by using fit fall trap and sweeping net method by comparing of mustard plants applied by PGPR with control. The application of PGPR biodiversity affects the diversity of visitors Arthropod mustard plants, where as many as 9 species of arthropods found in mustard plant control while in mustard plants with PGPR application only found 3 species of Arthropods. The application of PGPR biological fertilizer also influences the abundance of Arthropod visitors of mustard plants, where the number of arthropods caught on controlled mustard plants is much higher than that of the mustard plants with PGPR treatment. Keywords: Abundance, Arthropods, Diversity, PGPR